Wireless Networks – Analysis on Prevention of Jamming Attacks (International Journal of Engineering and Computer Science, 2015)
Jamming a wireless communication device that transmits on the same frequency range as a cell phone to create strong cell tower interference and block cell phone signals and call transmission. Jammers are usually undetectable and may experience minimal effects such as poor signal reception and devices may be used in any location but are typically deployed where cell phone use may be disruptive or wireless may get vulnerable to interference attacks. To prevent from jamming in any communication hiding the information is the best concern typically jamming has been addressed under an external threat model.Adversary is a short period of time, jammer selectivelytargeting messages of priority high importance. Our analysis providesprevention of jamming in terms of network performance degradation andeffort by presenting machine learning algorithm like clustering & Classification, a selective attack on wireless network on routing. We show comparative work on jamming attacks can belaunched by performing real-time packet classification. Cryptographic primitive is hides the data, to mitigate the attacks prevents real time packet classification, provides the security communication.